The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1161/01.cir.102.10.1126
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Improving Prognosis in Heart Failure

Abstract: Background-Contemporary survival in unselected patients with heart failure and the population impact of newer therapies have not been widely studied. Therefore, we have documented case-fatality rates (CFRs) over a recent 10-year period. Methods and Results-In Scotland, all hospitalizations and deaths are captured on a single database. We have studied case fatality in all patients admitted with a principal diagnosis of heart failure from 1986 to 1995. A total of 66 547 patients (47% male) were studied. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
93
1
9

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(111 citation statements)
references
References 25 publications
8
93
1
9
Order By: Relevance
“…In Montreal, in 1999, 85% of the hospitalizations for CHF were for people 65 years of age and older (33). Furthermore, the similarities in age distribution between men and women in these clinics is surprising, because epidemiological studies have shown that CHF develops later in life in women (30), who are older at diagnosis (34) and at first CHF hospitalization (13,35). We observed that only 27% of the patients in this study were women, even though the crude prevalence of CHF is similar between the sexes (28,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In Montreal, in 1999, 85% of the hospitalizations for CHF were for people 65 years of age and older (33). Furthermore, the similarities in age distribution between men and women in these clinics is surprising, because epidemiological studies have shown that CHF develops later in life in women (30), who are older at diagnosis (34) and at first CHF hospitalization (13,35). We observed that only 27% of the patients in this study were women, even though the crude prevalence of CHF is similar between the sexes (28,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 64%
“…Women represent more than one-half of these CHF hospitalizations (2); thus, it is important to determine whether there are sex-related inequities in the referral and follow-up of CHF patients. A sex-related bias in access to services has been documented in coronary artery disease (3-8) and, to a lesser extent, in CHF (9-12).In the past decade, new developments in treatment have led to improvements in CHF survival, decreased hospital admissions and improved quality of life (13,14). To implement these new treatment regimens, and to account for the growing number of cases and hospitalizations, specialized, multidisciplinary CHF clinics have been established.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HF is a complex clinical syndrome and it is the final and most severe manifestation of nearly every form of heart disease (4,5). The prognosis of HF is particularly poor, with fewer than 50% of subjects remaining alive by 5 years, and only 10% by 10 years following the initial diagnosis (14)(15)(16)(17). Likewise, we recently found that HF is an important contributor to the excess overall mortality in RA (Crow- …”
Section: Discussionmentioning
confidence: 99%
“…However, over the past two decades there has been a substantial reduction in mortality, probably due to more widespread use of renin-angiotensin aldosteron (RAAS) and beta-receptor blocking agents [2,4,5]. Studies from Sweden and from Scotland have shown that the prognosis has improved [6][7][8]. With an ageing population, however, the impact of HF on individual health and health care systems is still profound.…”
Section: Introductionmentioning
confidence: 99%